2018
DOI: 10.1177/1534735418794885
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Treatments for the Prevention of Chemotherapy- and Radiotherapy-Induced Mucositis

Abstract: Background: Chemoradiotherapy-associated mucositis can manifest as pain, inflammation, dysphagia, diarrhea, weight loss, rectal bleeding, and infection. Mucositis is a major dose-limiting side effect of chemotherapy, affecting nutritional intake and oral and intestinal function. Despite several interventions being available, there is a need for safe and effective preventative and treatment options for treatment-induced mucositis. The goals of this review are to discuss interventions based on foods and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 143 publications
2
80
0
4
Order By: Relevance
“…With respect to cancer treatment including chemotherapy and radiotherapy, a recent study has reported that over 80% of patients treated with 5-fluorouracil developed gastrointestinal mucositis [28]. It is well documented that both radiotherapy and chemotherapy including 5-fluorouracil or oxaliplatin could cause gastrointestinal toxicities such as direct epithelial injury, tissue ischemia, villi shortening, increased crypt depth, apoptosis of intestinal epithelial cells, and bacterial translocation [28][29][30][31][32][33]. In addition, cancer treatment might have a marked effect on gut microbiota, leading to intestinal dysbiosis, mucositis, and bacterial translocation [34].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to cancer treatment including chemotherapy and radiotherapy, a recent study has reported that over 80% of patients treated with 5-fluorouracil developed gastrointestinal mucositis [28]. It is well documented that both radiotherapy and chemotherapy including 5-fluorouracil or oxaliplatin could cause gastrointestinal toxicities such as direct epithelial injury, tissue ischemia, villi shortening, increased crypt depth, apoptosis of intestinal epithelial cells, and bacterial translocation [28][29][30][31][32][33]. In addition, cancer treatment might have a marked effect on gut microbiota, leading to intestinal dysbiosis, mucositis, and bacterial translocation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, efficacy and safety of oral zinc sulfate for chemotherapy-induced oral mucositis remain controversial. It must be noted, however, that it is essential to investigate separately the efficacy of oral zinc sulfate in the prevention and treatment of chemotherapy-induced oral mucositis because differences between radiotherapy and chemotherapy cannot be ignored ( 14 ). We consequently performed this systematic review and meta-analysis to comprehensively assess the efficacy and safety of zinc sulfate for chemotherapy-induced oral mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent studies have investigated the positive effects of Lactobacillus brevis CD2 lozenges on the severity and prevalence of mucositis, as well as the tumor resistance to radiotherapy. It was observed that patients who received Lactobacillus during chemotherapy had fewer intestinal problems than the others, resulting in shortening the course of chemotherapy and lower doses . Another method to reduce the side effects of chemotherapy is the COBALT strategy (combination bacteriolytic therapy; simultaneous use of C novyi ‐ NT spores with conventional chemotherapeutic agents).…”
Section: Combination Of Bacteriotherapy With Chemotherapymentioning
confidence: 99%